2017
DOI: 10.3389/fnhum.2017.00314
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Human Workload from the Auditory Steady-State Response Recorded via a Wearable Electroencephalography System during Walking

Abstract: Workload in the human brain can be a useful marker of internal brain state. However, due to technical limitations, previous workload studies have been unable to record brain activity via conventional electroencephalography (EEG) and magnetoencephalography (MEG) devices in mobile participants. In this study, we used a wearable EEG system to estimate workload while participants walked in a naturalistic environment. Specifically, we used the auditory steady-state response (ASSR) which is an oscillatory brain acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
0
22
2
Order By: Relevance
“…On the other hand, the B group showed almost no significant differences between tasks. Previous studies reported that ITCs decrease with increasing difficulty during tasks of different difficulty while listening to 40-Hz pulses (Griskova-Bulanova et al, 2011;Yokota and Naruse, 2015;Yokota et al, 2017). As SI experience grows, interpreters focus on the target stimuli during multitasking (Strobach et al, 2015;Henrard and Daele, 2017;Van der Linden et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the B group showed almost no significant differences between tasks. Previous studies reported that ITCs decrease with increasing difficulty during tasks of different difficulty while listening to 40-Hz pulses (Griskova-Bulanova et al, 2011;Yokota and Naruse, 2015;Yokota et al, 2017). As SI experience grows, interpreters focus on the target stimuli during multitasking (Strobach et al, 2015;Henrard and Daele, 2017;Van der Linden et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…However, body movements and measurement sounds cause much noise. In recent years, the development of active electrodes and portable EEG has made it possible to measure brain function in situations closer to realistic environments, such as while walking (Yokota and Naruse, 2015 ; Yokota et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study (Yokota et al, 2017), the load effect on ITC varied with time on task: The ITC was higher during low load than during high load only in the first half of the experiment. To determine whether the load effect varied over time, we conducted exploratory ANOVAs of load (2 levels: low vs. high) by block (4 levels), as shown in the Supporting Information.…”
Section: Effect Of Timementioning
confidence: 90%
“…Only a few previous studies have tested the effects of crossmodal attention on 40‐Hz ASSRs by manipulating the difficulty or load of the visual task. These visual tasks had several different load levels: detecting an easy versus difficult target (Parks, Hilimire, & Corballis, 2011), detecting versus discriminating a change in target brightness (de Jong, Toffanin, & Harbers, 2010), reading versus performing a visual search task (Griskova‐Bulanova, Ruksenas, Dapsys, Maciulis, & Arnfred, 2011), playing an easy versus difficult Tetris game (Roth et al., 2013), flying an airplane in a flight simulator during self‐reported low versus high mental workload (Tsuruhara, Arake, Ogawa, Aiba, & Tomitsuka, 2015), and performing n ‐back tasks with different n to vary the difficulty (Yokota & Naruse, 2015; Yokota, Tanaka, Miyamoto, & Naruse, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation